Evaluation of two rapid methods for identifying and biotyping Haemophilus influenzae. Issue 7 (July 1990) - Murphy, P G; Craig, I; Lafong, A C; Smyth, E T
Abstract : Several rapid method kits (one to four hours) have become available for the identification of Haemophilus and related genera. Two kits (the "Rapid NH" system and the "RIM Haemophilus" system), which include the identification and biotyping of H influenzae, were investigated for the rapid identification and biotyping of 193 isolates of H influenzae and the results compared with those obtained by more standard overnight methods. The kits were convenient to use and gave reliable and rapid speciation of all isolates. Both test systems were unreliable for biotyping: 42 isolates were wrongly biotyped by the RIM kit and 40 isolates wrongly biotyped by the rapid NH kit. It is concluded that the test kits may be useful for the rapid identification of H influenzae but that they are not reliable for the biotyping of this species.